Uganda : Seventh Review Under the Policy Support Instrument, Request for a New Policy Support Instrument and Cancellation of Current Policy Support Instrument; Staff Report; Staff Supplements; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Seventh Review Under the Policy Support Instrument (PSI) for Uganda. The medium-term outlook for Uganda remains favorable but risks are on the rise. Growth is expected to rebound to its potential in the coming two years on the heels of a supportive fiscal stance and higher global and regional growth. It remains vulnerable to exogenous shocks as well as to election-related uncertainties. IMF staff supports the authorities' request for a new three-year PSI to anchor their near- and medium-term policies.